The stability of binary Al12X nanoclusters (X = Sc and Ti): superatom or Wade's polyhedron. (19th November 2018) - Tsunoyama, Hironori; Akutsu, Minoru; Koyasu, Kiichirou; Nakajima, Atsushi
Abstract: Binary nanoclusters (NCs) exhibit strong potential as building blocks for tailor-made scientific materials based on the precise tuning of their electron countings and spin states along with the synergistic effects that originate from the constituent elements. Herein, we studied the electronic and geometric structures of transition metal (TM) doped aluminum (Al) Al12 X NCs (X  =  Sc and Ti), which are binary systems that extend from representative superatom anions. On the basis of the photoelectron spectroscopy (PES) and density functional theory (DFT) calculations, Al12 X anion and neutral structures are characterized as vertex-replaced icosahedron. The highly stable exohedral Al12 X icosahedron is described based on an electron counting rule derived from the coupling of Wade–Mingos' rule and the jellium model.